Incentive compatible financial contracts, asset prices, and the value of control - Lacker, Jeffrey M; Levy, Robert J; Weinberg, John A (Journal of Financial Intermediation, 1990)
We examine a general equilibrium model of asset prices in the presence of a simple informational imperfection. Assets are productive only when combined with managerial services. A manager “controls” an asset; he can conceal some of the output at a cost. This limits the extent to which managers can shed risk by issuing claims. Incentive compatibility drives a wedge, the “value of control”, between physical and financial asset values. Equilibrium allocations can be supported by alternative specifications of the right to “name the next manager”. If this right is assigned to holders of claims, then financial asset prices exhibit “excess volatility.”